The need for mechanical ventilation in a child exposed to a laundry detergent pod - Kamit-Can, Fulya; Alparslan, Caner; Anıl, Ayşe Berna; Anıl, Murat; Zengin, Neslihan; Can, Ender (The Turkish Journal of Pediatrics, 2016)
Laundry detergent pods (LDPs) are a new, concentrated form of detergent covered by a membrane of polyvinyl alcohol or other water-soluble material. In contrast to traditional laundry detergents, the spectrum of responses to exposure to LDPs ranges from mild to life-threatening events. This is a case report of a 3-year-old male who ingested part of an LDP, leading to a depressed level of consciousness, upper airway obstruction, and severe respiratory distress. The patient required intubation and mechanical ventilation for 2 days before being discharged. This rare, severe clinical pattern demonstrates the potential toxicity of these laundry detergents. In the literature, few cases that required intubation and ventilation have been reported. To our knowledge, this is also the first case of LDP exposure reported from Turkey.
Keywords: critically ill children; laundry detergent pod; mechanical ventilation; poisoning